Emergence of Bluetongue Virus Serotype 3 in Portugal (2024) - Sílvia C. Barros; Ana Margarida Henriques; Fernanda Ramos; Tiago Luís; Teresa Fagulha; André Magalhães; Inês Caetano; Fábio Abade dos Santos; Filipa O. Correia; Carlos C. Santana; Ana Duarte; Ruben Villalba; et al. (Viruses)
In September 2024, bluetongue virus serotype 3 (BTV-3) was first identified in Portugal, specifically in the Alentejo region (Évora District), using molecular diagnostic methods. The initial case involved a sheep exhibiting severe clinical symptoms, including head oedema, prostration, nasal discharge, and significant respiratory distress. A subsequent case was documented in another sheep from a different farm within the same district, which presented with high fever (41.5 °C), nasal discharge, and arthritis, ultimately resulting in mortality. Within one month of these initial detections, additional cases in both sheep and cattle were reported in neighbouring districts, indicating the virus rapid spread within the region. In response to this emerging threat, extensive monitoring efforts are being undertaken to delineate the distribution of BTV-3, and vaccination campaigns targeting this serotype have been initiated. These measures aim to mitigate the impact of the virus on livestock health and prevent further transmission.